Physiological Changes and Yield Components of Safflower (Carthamus tinctorius L.) Lines as a Function of Water Deficit and Recovery in the Flowering Phase - de Almeida Silva, Marcelo [UNESP]; Santos, Hariane Luiz [UNESP]; de Sousa Ferreira, Lusiane [UNESP]; Silva, Dayane Mércia Ribeiro [UNESP]; dos Santos, Jania Claudia Camilo; de Almeida Prado Bortolheiro, Fernanda Pacheco [UNESP] (MDPI, 2023)
Since climate changes have caused water restrictions, safflower stands out as an alternative crop due to its adaptability to restrictive soil and climate conditions. Thus, this research aimed to evaluate the physiological and yield performance of four safflower lines (IMA 02, IMA 04, IMA 14, and IMA 21) under two water regimes [without water deficiency—around 22% soil moisture content—100% of field capacity (FC); and with water deficiency—50% of FC]. The water regimes were imposed for 30 days during the flowering phase, followed by rehydration for 20 days. Water deficiency decreased relative water content, water potential, photosynthetic pigment contents, photosynthetic performance, maximum variable and potential quantum yield of PSII, electron transport rate, and photochemical quenching. In contrast, it increased electrolyte leakage, water use efficiency, and non-photochemical quenching. The decreases in photochemical efficiency and photosynthetic performance as a function of water deficiency caused reductions in the number of capitula, 100-grain mass, and harvest index, with more significant reductions in IMA 02, which was considered susceptible to soil water changes. IMA 04, IMA 14, and IMA 21 were considered tolerant because their physiological variables and yield components were less affected by water restriction, and they also showed recovery after rehydration compared to IMA 02. Thus, these lines can be recommended for commercial use, and safflower breeding programs aiming to select superior genotypes under drought conditions.
Keywords: Carthamus tinctoriusL; chlorophyll a fluorescence; gas exchange; water restriction; yield components